Pengolahan Sampah Organik Skala Rumah Tangga di Dusun Drojogan - Farida Farida; Wildan Fauzi Husna; Nanang Arfianto; Salsabila Aulia Widyasmara; Astuti Catur Sari; Anas Setyawan (Universitas Mathla'ul Anwar Banten, 2021)
HOUSEHOLD SCALE ORGANIC WASTE PROCESSING IN DROJOGAN HAMLET. Garbage is generated from all activities in homes, offices, markets and various other places. The issue of waste should be of particular concern, so it needs to be addressed from all parties. The purpose of this devotional activity is to increase the role of community to ward off organic waste in household and raise public awareness to create a clean and healthy environment. The method used is to socialize, training and mentoring continuously to the partner community of PKK in RT 03 / RW03 Drojogan, Bumirejo, Mungkid, Magelang. This activity is carried out by providing training in the manufacture of organic compost fertilizer, liquid organic fertilizer and also greenhouse making. The result of this activity is increased knowledge and skills in processing organic waste into compost fertilizer, liquid fertilizer and the establishment of a green house.